Dietary conjugated linoleic acid alters oxidative stability and alleviates plasma cholesterol content in meat of broiler chickens - Ramiah, Suriya Kumari; Goh, Yong Meng; Ebrahimi, Mahdi (Hindawi Publishing Corporation, 2014)
This study was conducted to investigate the effects of dietary conjugated linoleic acid (CLA) on fatty acid composition, lipoprotein content, lipid peroxidation, and meat colour of broiler chickens. A total of 180 broiler chickens were allocated to 3 dietary treatments (0, 2.5, and 5% Lutrell) and given a standard broiler starter diet and finisher diet. Body weight of chickens and feed intake were recorded weekly. After slaughter, the breast meat was aged at 4°C for 0, 3, and 6 days. The fatty acid composition was measured in the breast meat. Body weight (BW) and feed efficiency were decreased by dietary CLA level (P < 0.05). Chicken fed with 2.5% Lutrell had the highest feed intake compared to the control (CON) group. The total CLA increased significantly (P < 0.05) in breast meat from birds supplemented with CLA. Propensity for lipid peroxidation was significantly higher after 6 days of meat storage (P < 0.05) and the redness in chicken breast meat was lower in CLA-fed birds (P < 0.05). It is also notable that a 5% Lutrell supplementation decreased the plasma total cholesterol (TC), low density protein (LDL), and HDL (high-density lipoprotein)/LDL ratio in chickens (P < 0.05).